Possibilities for overcoming COVID-19 – sociological analysis - Kineva, Todorka (Sociološki pregled, 2021)
Government’s anti-crisis measures are presented as a possibility to regulate and manage the Bulgarian economy and society during the Covid-19 crisis. The effects of their implementation to assist and support Bulgarian employers and unemployed people to handle the crisis are disclosed through empirical methods.
Keywords: Covid-19; crisis; opportunities; anti-crisis measures